STAT3 enhances the constitutive activity of AGC kinases in melanoma by transactivating PDK1 - Picco, María Elisa (2019)
Background: The PI3K/Akt and the STAT3 pathways are functionally associated in many tumor types. Both in vitro and in vivo studies have revealed that either biochemical or genetic manipulation of the STAT3 pathway activity induce changes in the same direction in Akt activity. However, the implicated mechanism has been poorly character‑ ized. Our goal was to characterize the precise mechanism linking STAT3 with the activity of Akt and other AGC kinases in cancer using melanoma cells as a model. Results: We show that active STAT3 is constitutively bound to the PDK1 promoter and positively regulate PDK1 tran‑ scription through two STAT3 responsive elements. Transduction of WM9 and UACC903 melanoma cells with STAT3small hairpin RNA decreased both PDK1 mRNA and protein levels. STAT3 knockdown also induced a decrease of the phosphorylation of AGC kinases Akt, PKC, and SGK. The inhibitory efect of STAT3 silencing on Akt phosphorylation was restored by HA-PDK1. Along this line, HA-PDK1 expression signifcantly blocked the cell death induced by dac‑ arbazine plus STAT3 knockdown. This efect might be mediated by Bcl2 proteins since HA-PDK1 rescued Bcl2, Bcl-XL, and Mcl1 levels that were down-regulated upon STAT3 silencing. Conclusions: We show that PDK1 is a transcriptional target of STAT3, linking STAT3 pathway with AGC kinases activity in melanoma. These data provide further rationale for the ongoing efort to therapeutically target STAT3 and PDK1 in melanoma and, possibly, other malignancies.